High performance blended membranes using a novel preparation technique - Idris, Ani; Mohd. Yusof, Noordin; Rashid, Roslina; Ahmed, Iqbal (Faculty of Chemical and Natural Resource Engineering, 2008)
The possibility of applying novel microwave (MW) technique in the dissolution of polyethersulfone (PES) and lithium halides in aprotic solvent is studied. The lithium halides additives used are lithium fluoride (LiF), lithium bromide (LiBr) and lithium chloride (LiCl) and a comparison is made with conventional method. PES was dissolved in dimethylformamide (DMF) in the single solvent whilst for the double solvent (DS); PES was dissolved in a mixture of two different solvents DMF and acetone. The concentrations of lithium halide in both solvents were varied from 1 to 5 wt%. In order to illuminate the mechanism through which lithium halide influences the kinetic membrane performance in both techniques, rheological, FTIR, contact angle and water uptake analysis were performed. The performances of the membranes were evaluated in terms of pure water permeation (PWP), permeation rate (PR) and separation rates of various polyethylene glycols. Result revealed that the hollow fiber MW membrane with the 3 wt% LiBr additive exhibits both high permeation rates of 222.16 Lm-2hr-1 and separation rates of 99% and molecular weight cutoff (MWCO) of 2.6 kDa. In general, the MW membranes exhibited higher permeation and separation rates compared to conventional electrothermal heating (CEH) membranes. The FTIR, contact angle and water uptake measurement revealed that the LiCl and LiBr have enhanced the hydrophilic properties of the PES membranes thus producing membrane with high permeation and separation rates.